Association between sleep duration and cardiovascular risk: the EVasCu cross-sectional study - Martínez-García, Irene; Saz-Lara, Alicia; Cavero-Redondo, Iván; Otero-Luis, Iris; Gómez-Guijarro, María Dolores; Moreno-Herraiz, Nerea; López-López, Samuel; Pascual-Morena, Carlos (Frontiers in Physiology, 2024)
Introduction Some cardiovascular risk markers have been associated with alterations in sleep duration in different populations; however, there is little evidence in a healthy population. Aim The aim of the present study was to analyze the associations between sleep duration and cardiovascular risk biomarkers, including advanced glycation end-products (AGEs) measured by skin autofluorescence (SAF), maximum carotid intima-media thickness (IMTMax), aortic pulse wave velocity (a-PWV), pulse pressure (PP), and low-density lipoprotein cholesterol (LDL-C), in healthy adults (EVasCu study). Methodology The EVasCu study included 390 participants. Simple and multiple linear regressions were performed between sleep duration and cardiovascular risk markers. ANOVA analysis and ANCOVA analysis adjusted for various covariates were then performed after categorizing sleep into 6 hours, 6-8 hours and >8 hours. Results 296 participants were included in the analyses (43.97 ± 12.60 years, 63.9% female). Simple linear regressions showed an inverse association between sleep duration and SAF, IMTMax, aPWV and PP. However, in the multiple linear regression with all the covariates, the statistical significance was lost. For its part, in the ANOVA analyses, sleep duration was also associated with the same parameters, but when performing the fully adjusted ANCOVA analyses, the statistical significance for SAF was maintained (p = 0.015), obtaining a difference of 0.223 arbitrary units (p = 0.017) when comparing the group < 6 hours vs. > 8 hours. Finally, there was no association for LDL-C. Conclusions An inverse association was found between sleep duration and APS, which is considered a marker of cardiovascular risk. Although prospective studies are needed, it is suggested that insufficient sleep may increase cardiovascular risk, which could be a key factor in future public health policies to promote health and prevent CVD.